The return of public health to local government in England: changing the parameters of the public health prioritization debate?. Issue 9 (September 2015) - Marks, L.; Hunter, D.J.; Scalabrini, S.; Gray, J.; McCafferty, S.; Payne, N.; Peckham, S.; Salway, S.; Thokala, P.
Abstract Objectives To explore the influence of values and context in public health priority-setting in local government in England. Study design Qualitative interview study. Methods Decision-makers' views were identified through semi-structured interviews and prioritization tools relevant for public health were reviewed. Interviews (29) were carried out with Health and Wellbeing Board members and other key stakeholders across three local authorities in England, following an introductory workshop. Results There were four main influences on priorities for public health investment in our case study sites: an organizational context where health was less likely to be associated with health care and where accountability was to a local electorate; a commissioning and priority-setting context (plan, do, study, act) located within broader local authority priority-setting processes; different views of what counts as evidence and, in particular, the role of local knowledge; and debates over what constitutes a public health intervention, triggered by the transfer of a public health budget from the NHS to local authorities in England. Conclusions The relocation of public health into local authorities exposes questions over prioritizing public health investment, including the balance across lifestyle interventions and broader action on social determinants of health and the extent to which the public health evidence base influences local democratic decision-making. Action on wider social determinants reinforces not only the art and science but also the values and politics of public health.